2011 37th IEEE Photovoltaic Specialists Conference 2011
DOI: 10.1109/pvsc.2011.6185961
|View full text |Cite
|
Sign up to set email alerts
|

A test protocol to enable comparative evaluation of maximum power point trackers under both static and dynamic irradiance

Abstract: The effectiveness of maximum power point trackers (MPPTs) is an important factor in the energy harvest economics of a PV system. Inverter manufacturers want to maximize the effectiveness of their MPPTs, and plant developers desire to choose inverters with the highest energy harvest to maximize their return on investment. However, comparing MPPTs against one another is challenging because the most common figure of merit, the MPPT efficiency, depends on the characteristics of the PV array and on the time variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Ropp et al proposed a profile for evaluating the performance of MPPT algorithms. Their test protocol consists of slow ramps, fast ramps, and steady-state conditions [14]. Bründlinger et al also suggested a test sequence for the MPPT techniques where the PV inverter and its efficiency are included into their considerations and evaluations [15].…”
Section: Testing Criteria Of Mppt Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ropp et al proposed a profile for evaluating the performance of MPPT algorithms. Their test protocol consists of slow ramps, fast ramps, and steady-state conditions [14]. Bründlinger et al also suggested a test sequence for the MPPT techniques where the PV inverter and its efficiency are included into their considerations and evaluations [15].…”
Section: Testing Criteria Of Mppt Algorithmsmentioning
confidence: 99%
“…The question is how realistic such approaches are if we were to compare them against our measurement data. We obtain, for example for r λ,u , from [14]: for steady-state conditions: r λ,u = 0 W m 2 /s for slow ramps:…”
Section: Testing Criteria Of Mppt Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these methods have some disadvantages. For example, perturb and observe P&O algorithm fails to track the MPP in case of rapid environmental changes, and incremental conductance IC oscillates around the MPP [1][2][3]. Some techniques use look up tables, consequently more memory space is required, like the analytical solution for tracking photovoltaic module MPP used in [4].…”
Section: Introductionmentioning
confidence: 99%